2013
DOI: 10.1016/j.bpj.2012.11.3828
|View full text |Cite
|
Sign up to set email alerts
|

Microdomains Shift and Rotate in the Lateral Wall of Cochlear Outer Hair Cells

Abstract: Outer hair cell (OHC) electromotility, a response consisting of reversible changes in cell length and diameter induced by electrical stimulation, confers remarkable sensitivity and frequency resolution to the mammalian inner ear. Looking for a better understanding of this mechanism, we labeled isolated guinea pig OHCs with microspheres and, using high-speed video recording, investigated their movements at the apical, mid, and basal regions of osmotically and electrically stimulated cells. After hypoosmotic cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
(65 reference statements)
1
4
0
Order By: Relevance
“…3 C), suggesting that the RhoA/ROCK/PKCa pathway is continuously at work, even in the absence of external LPA stimulation, to regulate the motile response of cochlear OHCs. As described in previous studies (4,13), under the three experimental conditions the electromotile amplitude increased with time, reached a plateau~2 s after stimulation, and then remained stable. Here, we report data obtained from up to 3 s of electrical stimulation, the same final time point used in the previous studies.…”
Section: Bim-1 Inhibits the Changes In Ohc Motility Induced By Lpasupporting
confidence: 81%
See 1 more Smart Citation
“…3 C), suggesting that the RhoA/ROCK/PKCa pathway is continuously at work, even in the absence of external LPA stimulation, to regulate the motile response of cochlear OHCs. As described in previous studies (4,13), under the three experimental conditions the electromotile amplitude increased with time, reached a plateau~2 s after stimulation, and then remained stable. Here, we report data obtained from up to 3 s of electrical stimulation, the same final time point used in the previous studies.…”
Section: Bim-1 Inhibits the Changes In Ohc Motility Induced By Lpasupporting
confidence: 81%
“…Outer hair cells (OHCs) have the ability to continuously adjust their total length and the amplitude of their electrically induced somatic movements to optimize the sensitivity and frequency selectivity of the mammalian cochlea (1). We have used the term ''mechanical homeostasis'' to identify this process (2), and our previous studies provided strong evidence that it involves finely regulated cytoskeletal changes mediated by Rho GTPases (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Latrunculin A has been reported to disrupt F-actin in OHC lateral wall in cochlear explant culture at P0 and P3 [ 28 ] and diamide has been reported to reduce OHC stiffness [ 29 ]. In addition, when OHCs were treated with 5 μM Y-27632 (a RHO inhibitor [ 30 ]), no change in Slc26a5’s lateral mobility was observed ( S5G and S5H Fig ). These results suggest that cytoskeletal structures alone are unlikely to control Slc26a5’s lateral mobility.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, collapsed trilaminate structure by both salicylate and MβCD can remove a key constraint on membrane proteins in the lateral wall of OHCs. In support, OHC electromotility is diminished and ultimately abolished when OHCs become flaccid [ 2 , 45 , 46 ], and polystyrene microspheres labeled membrane in lateral wall become re-oriented towards cell’s longitudinal axis when a quiescent OHC is electrically stimulated [ 30 ]. Together, these results strongly support that the integrity of the organized trilaminate structure constitutes the main factor that coordinate the orientation of the Slc26a5 motor units in the OHC lateral wall and endow the greater axial than radial electromotile response.…”
Section: Discussionmentioning
confidence: 99%
“…The anisotropy of lipid lateral diffusion in the OHC plasma membrane has a major axis that is on average parallel to the OHC axis [10] suggesting that spectrin slows down circumferential diffusion. It has recently been shown that electrically evoked displacements of nanobeads on the OHC plasma membrane reorient in response to electrical stimulation becoming axial over time [14]. The evidence suggests the OHC matrix serves to coordinate and orient membrane motor activity.…”
Section: Neuronal Axons and The Outer Hair Cell Lateral Wall Have Simmentioning
confidence: 99%